Brand differentiation of selected feminine wash brands as perceived by young professionals in district III of Manila - Bagano,Lalaine Joy M. Calimlim,Esperanza S. Caliwag,Mary Jennifer Z. Fama,Precious A. Guerra,Ma. Criselda R. Pamplona,Alexander S. Santiago,Lara Bianca C. Sebastian,Wilfredo B. and VillenaZussane Marie T. 4 0 16; 5 (2010)
u
Research Paper: (BSBA major in Marketing) - Pamantasan ng Lungsod ng Maynila 2010.
Keywords: 2 -- 0; 6; 20; 20; 2